2009
DOI: 10.1111/igc.0b013e3181a83135
|View full text |Cite
|
Sign up to set email alerts
|

Gedunin, a Novel Natural Substance, Inhibits Ovarian Cancer Cell Proliferation

Abstract: The discovery of more active therapeutic compounds is essential if the outcome for patients with advanced-stage epithelial ovarian cancer is to be improved. Gedunin, an extract of the neem tree, has been used as a natural remedy for centuries in Asia. Recently, gedunin has been shown to have potential in vitro antineoplastic properties; however, its effect on ovarian cancer cells is unknown. We evaluated the in vitro effect of gedunin on SKOV3, OVCAR4, and OVCAR8 ovarian cancer cell lines proliferation, alone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 21 publications
2
50
0
Order By: Relevance
“…Other studies have shown toxic properties of limonoids on insect larvae [30,31]. More specifically, gedunin and some of its derivatives have been investigated for antimalarial, hepatoprotective, and antitumor properties [32][33][34]. Anti-inflammatory, analgesic, and antiallergic virtues of the oil have led to the development of pharmaceutical products [35].…”
Section: Propertiesmentioning
confidence: 99%
“…Other studies have shown toxic properties of limonoids on insect larvae [30,31]. More specifically, gedunin and some of its derivatives have been investigated for antimalarial, hepatoprotective, and antitumor properties [32][33][34]. Anti-inflammatory, analgesic, and antiallergic virtues of the oil have led to the development of pharmaceutical products [35].…”
Section: Propertiesmentioning
confidence: 99%
“…Caspase-dependent Cleavage of p23-Gedunin has been reported to induce cancer cell death in prostate, ovarian, and colon cancer cell lines (21)(22)(23). Data in Fig.…”
Section: Gedunin Induces Apoptotic Death Of Cancer Cells Andmentioning
confidence: 99%
“…3A) that is isolated from the Meliacae family of medicinal plants and has been used for the treatment of malaria and other infectious diseases in traditional Indian medicine. Recent reports have shown that gedunin exhibits anti-proliferative activity against tumor cells from prostate, ovarian, and colon origins (21)(22)(23). Connectivity map analysis established that gedunin is an inhibitor of the Hsp90 machine (24) via a yet unknown mechanism, which is distinct from that of ansamycin analogues (23).…”
mentioning
confidence: 99%
“…Gedunin and its analogs are an important bioactive limonoid-type tetranortriterpene isolated from the Meliaceae family and are reported to display a wide range of biologic activities, including antitumor, antimalarial, antiallergic, and anti-inflammatory activity in different experimental models (Brandt et al, 2008;Kamath et al, 2009;Ferraris et al, 2011Ferraris et al, , 2012Miranda Júnior et al, 2012;Henriques and Penido, 2014;Conte et al, 2015). The molecular mechanism of action related to the biologic effects of gedunin relies on the inhibition of Hsp90 activity via specific binding to the cochaperone p23 and by disrupting the cochaperone Cdc37-Hsp90 interaction (Matts et al, 2011;Patwardhan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%